The Vertical Profile Of Phosphate In Pinang Dalam Lake Buluh China Village Siak Hulu Sub District Kampar District Riau Province - Artauli Sigalingging; Madju Siagian; Clemens Sihotang (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study has been done in Pinang Dalam Oxbow Lake from January-February 2014. This research aims to understand the vertical profile of phosphatein Pinang Dalam oxbow lake. The research used survey method. The sample’swere taken from three station, the first station were at inlet, the second stationwere at middle of lake and the third station were at the end of lake. The measuringquality water parameters were depth, transparency, temperature, pH, dissolvedoxygen (DO), carbon dioxide and nitrate. Sampling vertical based ontransparency, namely at surface, 11/2Secchi depth, 21/2Secchi depth, and in thebottom of lake. The result shown the concentration of phosphate at the surface:0.03-0.04 Mg/L; in the 11/2Secchi depth: 0.07-0.09 Mg/L; in the 21/2Secchi depth:0.12-0.15 Mg/L and the bottom of lake: 0.15-0.19 Mg/L. The vertical profile ofphosphate showed the concentration increased with the increment of depth. Thewater quality parameter analyzed were temperature: 28oC–28.34oC; transparancy52.5-54.34 cm; depth: 180.67–429 cm; pH: 5; dissolved oxygen (DO): 1.64-5.88Mg/L; carbon dioxide: 6.79–14.65 Mg/L; nitrate: 0.01-0.13 Mg/L, andphytoplankton abudance: 3523363.7-4293075.48 cel/l. The concentration ofphosphate in Pinang Dalam Lake showed the tropic status was mesotropic and allthe water quality still support the aquatic organisms life.Keywords : Phosphate, the vertical profile, Pinang Dalam Lake